PENGARUH KOMBINASI PETROGENOL DAN SARI MANGGA HARUM MANIS TERHADAP FEEDING STRATEGY LALAT BUAH Bactrocera dorsalis H. - Fransiska, Maria; Sumarmin, Ramadhan; Zeswita, Armein Lusi (Pendidikan Biologi, 2013)
ABSTRACTMango fruit is a good fruit to use as an attractant to insect. The mango fruit contained simple sugars sucrose, glucose, and fructose and cellulose. Methyl eugenol is a compound of insect pheromones to attract the opposite sex for mating, colonize and to eat. However, the information about the mango juice and petrogenol ifman the imago to Bactrocera dorsalis feeding strategy still limited. The research aimed to determine the effect of mango juice and petrogenol to the imago Bactrocera dorsalis feeding strategy. This study is an experimental research used tubes Y. Method Feeding strategy observed were searching, grounding, and gathering. Data were analyzed using chi-square (X²) and compared to the 5% significance level. This study was conducted in July-August 2013,held at the Zoology laboratory of the Biology Department, Padang state university. The results showed that the feeding strategy Bactrocera dorsalis. Influenced by combination of mango juice with petrogenol. Best searching activity on ratio of 3:1, the best grounding in 1:2 ratio and gathering the best in the ratio of 1:3. It can be concluded that the combination petrogenol and mango juice are the best as attractants to fruit flies Bactrocera dorsalis.